Pengaruh Citra Merek dan Kualitas Produk terhadap Keputusan Pembelian Produk Pigeon Teens Skin Care Pada PT. Tiga Sepakat Mandiri - Dara Martania (Science of Management and Students Research Journal (SMS), 2020)
The research object focuses on the compact powder pigeon product, because the current solid powder has a change like two way cake, thus making consumers have a new option and slowly leave the compact powder. A lot of consumers are not aware that compact powder and two way cake is a different type of powder, although it has a relatively similar form but the content in these powders has a difference. Pigeon has a product that can meet the needs of teenagers. Based on simultaneous testing results (TestF) It is known that there is a significant influence between brand image (X1) and product quality (X2) together with the purchase decision (Y) at PT. Tiga Sepakat Mandiri in Jambi city. This is indicated by fcalculate greater than ftable of 3.175 from 3.14. Variable brand image (X1) and product quality (X2) is able to explain the change in Purchase decision (Y) on PT. Tiga agreed Mandiri in Meranti supermarket Jambi City by 9% while the remaining of 91% is influenced by other variables that are not included or Not addressed in this study. Based on the test results (T-Test) It is known that there is no significant influence between the brand image of purchase decision. Because the value of 0.814 Tcalculate is smaller than 1.669. And the Product quality variable (X2) is known to be a significant effect on the purchase decision (Y). This is evidenced by the value of Thitung greater than this amounting to 1.972 > 1.669.